Royal Flying Doctor Service. Season three [videorecording (DVD)] - Meadows, Ian, 1983-; Banks, Imogen; Fennessy, Mark (Seven Network, PBS Distribution, 2026)
In this season, the RFDS will grapple with the fallout of the domino effects of a tragedy- mental health issues, an unexpected pregnancy, an emergency amputation, drug addiction and the shocking acts of retribution that then arise. Everyone on the team must also navigate their own personal challenges while being wrapped up inextricably in their patients' lives. As the Broken Hill crew faces their toughest obstacles yet, they are forced to make tough decisions about what they want their lives to be and who they want to share them with.